2016
DOI: 10.1590/bjpt-rbf.2014.0188
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with attitudes and beliefs of elders with acute low back pain: data from the study Back Complaints in the Elders (BACE)

Abstract: BackgroundThe attitudes and beliefs that older people have about acute low back pain (LBP) may influence the coping mechanisms and the adoption of treatment strategies in this population.ObjectiveThe aim of this study was to identify the factors associated with the attitudes and beliefs of elderly patients with acute low back pain using the Back Beliefs Questionnaire.MethodThis is a cross-sectional study with a subsample of the study “Back Complaints in the Elders” (BACE), composed of 532 older Brazilians of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…This indicates that there was room for improvement in back pain beliefs in the current study 40. Another study that assessed factors that were associated with beliefs and attitudes of elderly (mean age 69) also found low LBP beliefs scores (mean 23.7) 41. In the current study disability scores measured with the RDQ-24 showed low levels of disability, and absenteeism rates were also low.…”
Section: Discussionsupporting
confidence: 47%
“…This indicates that there was room for improvement in back pain beliefs in the current study 40. Another study that assessed factors that were associated with beliefs and attitudes of elderly (mean age 69) also found low LBP beliefs scores (mean 23.7) 41. In the current study disability scores measured with the RDQ-24 showed low levels of disability, and absenteeism rates were also low.…”
Section: Discussionsupporting
confidence: 47%
“…It is part of the multicenter project named Back Complaints in the Elderly (BACE), a prospective observational epidemiological cohort study developed by an international consortium in the Netherlands, Australia, and Brazil. 11 , 12 This project was approved by the Ethics Committee of Universidade Federal de Minas Gerais (UFMG), Belo Horizonte, MG, Brazil (ETIC 0100.0.203.000-11).…”
Section: Methodsmentioning
confidence: 99%
“… 7 Regarding marital status, the literature indicates that, even without pain symptoms, married older adults had lower disability when compared to older adults living alone. 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that these differences could be due to some factors: younger adults were more active in the community, thus pain could have affected more significantly their daily functions; also, other factors influence pain and disability in the aged population, such as increased levels of inflammatory cytokines, 11 , 12 sarcopenia, 13 , 14 degenerative diseases, having poorer perception of health, psychosocial factors, and having more concurrent diseases. 15 , 16 , 17 Additionally, these results might also lie in the peculiarity of the evolution of life expectancy in Brazil, which in 1940 was around 40 years old. Thus, Brazilians aged 75 and over from this study must have physical and functional characteristics that favored their survival over the years, thus being more resilient to their health condition.…”
Section: Discussionmentioning
confidence: 99%